Montserrat JIMÉNEZ SUREDA, "Les bruixes: del feminicidi històric a l’icona social" [The witches. From historic feminicide to social icons]. Barcelona, Universitat Autonoma de Barcelona, 2017, 68 pp. - Ellmann, Sabrina (Tropelías: Review of Literary Theory and Comparative Literature, 2019)
The present paper is a book review about the literary treatment received by witchess all along history. The book it is based on has been written by doctor Montserrat Jiménez Sureda
Keywords: Witches; literature; Western World